2020
DOI: 10.1186/s40634-020-00235-9
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical testing of fixed and adjustable femoral cortical suspension devices for ACL reconstruction under high loads and extended cyclic loading

Abstract: Purpose: To compare loop elongation after 5000 cycles, loop-elongation at failure, and load at failure of the fixedloop G-Lok device and three adjustable-loop devices (UltraButton, RigidLoop Adjustable and ProCinch RT), during testing over extended cycles under high loading. Methods: Five devices of each type were tested on a custom-built rig fixed to an Instron machine. The testing protocol had four stages: preloading, cyclic preconditioning, incremental cyclic loading and pull-to-failure. Outcome measures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“… 1 In a recent study comparing UB with 2 other ALDs (RigidLoop Adjustable and ProCinch RT), after 5000 cycles, UB showed the largest elongation at failure, although all 3 demonstrated elongations <3 mm over an extended number of cycles at high loads. 36 However, Cheng et al 8 observed that the mechanical properties of the GraftMax ALD were comparable with those of TR.…”
Section: Discussionmentioning
confidence: 99%
“… 1 In a recent study comparing UB with 2 other ALDs (RigidLoop Adjustable and ProCinch RT), after 5000 cycles, UB showed the largest elongation at failure, although all 3 demonstrated elongations <3 mm over an extended number of cycles at high loads. 36 However, Cheng et al 8 observed that the mechanical properties of the GraftMax ALD were comparable with those of TR.…”
Section: Discussionmentioning
confidence: 99%
“…Primary stability of ALB button devices has been assessed in a variety of biomechanical studies with different study protocols. 20 , 36 , 41 First, isolated testing of the implant led to lower elongation and higher load to failure in comparison to in vitro ACLR. 6 , 12 , 19 , 24 , 36 However, the influence of the interface between the implant and the cortical bone or the tendon graft is not considered in isolated implant testing.…”
Section: Discussionmentioning
confidence: 99%
“…While an adjustable‐length femoral cortical fixation device can eliminate potential risks associated with the interference screw, such as intra‐articular migration and loss of fixation owing to screw–tunnel divergence, experimental studies have indicated that loop loosening induced by cyclic loads could be a concern [3, 13, 14, 16, 25, 32]. Alternatively, Kusano et al have evaluated CT images obtained 1 and 12 weeks after ART ACL reconstruction with a BTB graft and reported that the loop length change of BTB TightRope ® was negligible in a clinical setting, which was different from an experimental setting [21].…”
Section: Discussionmentioning
confidence: 99%